Ответ:
Объяснение:
1,25х -(0,25х + 2,45 х²)=1,25х - 0,25 х -2,45х²= х - 2,45 х²
х -(-х+у) = х + х -у=2х -у
-5d + d² - (-d +2d² +1)=-5d + d² +d -2d² -1= -d² -4 d -1
-3z +8 -( -9z² -3z +8)=-3z +8+9z² +3z -8= 9z²
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
1,25х -(0,25х + 2,45 х²)=1,25х - 0,25 х -2,45х²= х - 2,45 х²
х -(-х+у) = х + х -у=2х -у
-5d + d² - (-d +2d² +1)=-5d + d² +d -2d² -1= -d² -4 d -1
-3z +8 -( -9z² -3z +8)=-3z +8+9z² +3z -8= 9z²